A Note of Caution on Quantifying Banks' Recapitalization Effects - Kirsten Schmidt; Felix Noth; Lena Tonzer (Journal of Money, Credit and Banking, 2021)
Unconventional monetary policy measures like asset purchase programs aim to reduce certain securities' yield and alter financial institutions' investment behavior. These measures increase the institutions' market value of securities and add to their equity positions. We show that the extent of this recapitalization effect crucially depends on the securities' accounting and valuation methods, country-level regulation, and maturity structure. We argue that future research needs to consider these factors when quantifying banks' recapitalization effects and consequent changes in banks' lending decisions to the real~sector.
Keywords: 330; capital regulation; security valuation; unconventional monetary policy